A case of incomplete Kawasaki disease with extremely high serum ferritin and interleukin-18 levels - Takanori Noto (BMC Pediatrics, 2018)
Abstract Background The clinical features and laboratory parameters of patients with Kawasaki disease (KD) and systemic juvenile idiopathic arthritis (sJIA) occasionally overlap. Therefore, serum levels of cytokine and ferritin are used as markers to distinguish between KD and sJIA. KD patients have a high level of interleukin (IL)-6, low level of IL-18, and no elevation of the level of serum ferritin. Conversely, sJIA patients have a low level of IL-6 and high levels of IL-18 and ferritin in the serum. However, to the best of our knowledge, no case report of KD with a low serum level of IL-6 and extremely high levels of IL-18 and ferritin is found. Case presentation A 6-year-old boy presented with a history of fever for 9 days and a rash that appeared 7 days from the onset. He was diagnosed with incomplete KD because of fever, skin rash, oral cavity erythematous changes, and erythema and edema of the hands with laboratory findings of serum albumin level < 3.0 g/dL, elevated alanine aminotransferase level and leukocyturia. Intravenous immunoglobulin and prednisolone and oral aspirin were introduced on the 10th day. Fever subsided 1 day after initiating the treatment, but arthritis of both knees appeared in addition to hepatosplenomegaly. We suspected sJIA, as the serum level of ferritin was 19,740 ng/mL, IL-6 was < 3 pg/mL, and IL-18 was 132,000 pg/mL. Skin desquamation of the fingertips was observed 18 days from the onset; thus, he was finally diagnosed with incomplete KD with arthritis. At 32 days from the onset, we stopped the prednisolone therapy and no symptoms of relapse were observed afterwards. In the follow-up at 16 months from the onset, he had neither signs of active joint or skin involvement, nor cardiac involvement. Conclusions Although patients with sJIA generally have high serum levels of IL-18 and ferritin, this was a case of incomplete KD with extremely high serum levels of IL-18 and ferritin. Serum cytokine and ferritin are often used for the differential diagnosis of KD and sJIA. We need to recognize the existence of KD with high serum levels of IL-18 and ferritin.